2020
DOI: 10.1038/s41598-020-62180-y
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between steady-state visually evoked potentials at nearby flicker frequencies

Abstract: Steady-state visually evoked potential (SSVep) studies routinely employ simultaneous presentation of two temporally modulated stimuli, with SSVEP amplitude modulations serving to index top-down cognitive processes. However, the nature of SSVEP amplitude modulations as a function of competing temporal frequency (TF) has not been systematically studied, especially in relation to the normalization framework which has been extensively used to explain visual responses to multiple stimuli. We recorded spikes and loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
23
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 74 publications
8
23
3
Order By: Relevance
“…Insofar as the strength of target SSVEP signals when measured with EEG may reflect the strength of target-specific spike activity in the sensory cortex, our finding does challenge such theories that propose response strength is positively correlated with the vividness of conscious experience. Currently, however, the exact mechanisms of SSVEP generation are not well understood ( Kawashima et al, 2020 ; Kim et al, 2017 ; Norcia et al, 2015 ; Notbohm et al, 2016 ; Rager and Singer, 1998 ; Salelkar and Ray, 2020 ), and future studies will be necessary to clarify their input.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insofar as the strength of target SSVEP signals when measured with EEG may reflect the strength of target-specific spike activity in the sensory cortex, our finding does challenge such theories that propose response strength is positively correlated with the vividness of conscious experience. Currently, however, the exact mechanisms of SSVEP generation are not well understood ( Kawashima et al, 2020 ; Kim et al, 2017 ; Norcia et al, 2015 ; Notbohm et al, 2016 ; Rager and Singer, 1998 ; Salelkar and Ray, 2020 ), and future studies will be necessary to clarify their input.…”
Section: Discussionmentioning
confidence: 99%
“…For example, first-order theories of conscious perception (Mehta & Mashour, 2013;Zeki, 2007) propose that the strength of activity within contentspecific visual processing areas determines the vividness of that visual experience. Currently, however, the exact mechanisms of SSVEP generation are not well understood (Kawashima, Li, Chen, Vickery, & Morley, 2020;Kim et al, 2017;Norcia et al, 2015;Notbohm, Kurths, & Herrmann, 2016;Rager & Singer, 1998;Salelkar & Ray, 2020), and future studies will be necessary to clarify their input.…”
Section: Theories Of Consciousness and Visual Phenomenologymentioning
confidence: 99%
“…We chose 32 Hz SSVEP (induced by gratings of temporal frequency of 16 cycles per second or cps) for two reasons. First, in a separate set of experiments, we had recorded spikes and local field potentials (LFP) in the primary visual cortex of awake monkeys while presenting counterphasing gratings at varying temporal frequencies and found that the SSVEP gain was highest for gratings with temporal frequencies of 12 to 16 cps (Salelkar and Ray (2020)).…”
Section: Experimental Setup and Taskmentioning
confidence: 99%
“…where the transfer rate B can be translated into bits/minute, once it is multiplied by the frequency of decisions per minute T, as permitted in the BCI system shown in expression (21).…”
Section: Performance Metricsmentioning
confidence: 99%
“…On the other hand, the amplitude and phase of SSVEP responses are highly sensitive to stimulus parameters such as repetition rate, color, luminance or modulation depth, and spatial frequency [ 19 , 20 ]. However, the SSVEP paradigm stands out for its minimal training capacity; robustness, high signal-to-noise ratio (SNR); and high information transfer rate (ITR) [ 21 , 22 ]. Furthermore, for the analysis and design of BCI systems, it is necessary to consider three fundamental aspects: the short processing time, the high information transfer rate (ITR), and the fact that these should be as noninvasive as possible [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%